Reduced Resting and Increased Elevation of Heart Rate Variability With Cognitive Task Performance in Concussed Athletes. Issue 1 (January 2019) - Huang, Mu; Frantz, Justin; Moralez, Gilbert; Sabo, Tonia; Davis, Peter F.; Davis, Scott L.; Bell, Kathleen R.; Purkayastha, Sushmita
Abstract : Objective: To examine heart rate variability (HRV) at rest and with a 2-Back cognitive task involving executive function and sustained attention in athletes during the acute phase following concussion and compare them with the controls. Participants: Twenty-three male and female collegiate athletes (20 ± 1 years) following (4 ± 1 days) a sports-related concussion and 23 sports- and sex-matched noninjured controls. Procedure: Continuous R-R interval was acquired using 3-lead electrocardiogram for 3 minutes each at rest and during the 2-Back task. HRV was quantified as percent high-frequency (HF) power. Results: At rest, lower percent HF power was observed in the concussed athletes (23 ± 11) compared with the controls (38 ± 14; P = .0027). However, with the 2-Back task, an increase in HF power was observed in the concussed group (39 ± 12; P = .0008) from rest and was comparable with the controls (36 ± 15). No difference in HF power between rest and 2-Back task was observed in the controls. Conclusion: Lower HRV was observed at rest following concussion. An increase in HRV, suggestive of enhanced prefrontal cortex (PFC) functioning, was observed during a cognitive task in the concussed athletes. Therefore, cognitive tasks as early as 4 days after injury may increase PFC functioning from rest and expedite return to learn in collegiate athletes. Abstract : Supplemental Digital Content is Available in the Text.